Zoonotic potential of Chlamydia psittaci—a case report - Tomić, Danijela Horvatek; Krkljuš, Marija; Gottstein, Željko; Lozica, Liča; Prukner-Radovčić, Estella (Frontiers in Veterinary Science, 2026)
The causative agent of chlamydiosis/psittacosis, the obligatory intracellular bacterium C. psittaci, infects various species of birds and humans. Infected birds occasionally excrete the pathogen through the respiratory and digestive systems, with nasal/ocular discharge and feces being the main sources of infection for other birds or humans. Humans are most often infected through close contact with positive parrots. In this case report of avian chlamydiosis/psittacosis, samples were taken from a dead cockatiel and two budgerigars, and from a child living in the same household as the birds. In all the samples examined, except the child’s serum, C. psittaci was detected by real-time PCR. The phylogenetic analysis of the ompA gene from parrot isolates identified genotype A, confirming that parrots harbored the most virulent genotype of C. psittaci. To prevent the spread of avian chlamydiosis/psittacosis, it is necessary to procure birds from verified sources, monitor the signs of disease in parrots and humans, and strictly adhere to biosecurity measures to prevent further spread of the disease.